Bahaya Dan Pencegahan Infeksi Menular Seksual - Jenny Novina Sitepu (LPPM Universitas HKBP Nommensen, 2021)
Sexual transmitted infectiosn (STIs) is one of public health issue worldwide, both in industrial and developed country. Sexual transmitted infections control is one of World Health Organization priority because it become one of infection disease top 10 in developed country included Indonesia. The bad knowledge about sexual transmitted disease raise the risk of unsafe sexual activity by 1.7 times. Survei Demografi dan Kesehatan – Kesehatan Reproduksi Remaja 2017 showed that 68.8% 15-19 years old teenagers did not know about STIs, neither 55.7% 20-24 years old Indonesia citizens. This onlie seminar aimed to raise the pemuda-pemudi Gereja GMAHK Ramunia’s knowledge about sexual transmitted infections. Participants’ feedback showed that 86.7% pasticipants could understand the seminar’s content, and 93.3% participants agreed that this seminar is useful exspecially related to reproductive health.